Cardiac Implantable Electronic Device–Related Infection Due to Granulicatella adiacens. (14th March 2019) - Sendi, Parham; Wustmann, Kerstin; Büchi, Annina E; Noti, Fabian; Klaeser, Bernd; Sonderegger, Beat; Auf der Maur, Christoph; Mercier, Thomas; Schwerzmann, Markus; Ruppen, Corinne
Abstract: Cardiac implantable electronic device–related infection is clinically challenging. Curative treatment commonly includes system removal. A case caused by Granulicatella adiacens occurred in a 32-year-old woman. Clinical course, literature review, and biofilm investigations enabled successful antibiotic management without system removal.